Systems and procedures of Genpacco Incorporated - Arreola, Edylil (College of Engineering, 1994)
The main objective of the work study is to apply the tools and techniques learned in IE 32 in analyzing the existing system of a certain plant, to point out the problems, to search for alternatives involving these problems and to choose the best alternative to improve the existing system. The first part of the paper discusses the present process of Genpacco Incorporated in manufacturing cans mainly for food processors. Through analysis of the present state of the production system, with the use of charts and figures made by the team, the main problem which is poor plant layout was formulated. This main problem arose since no arrangement was planned beforehand. Having a poor plant layout resulted to inefficient storage methods, slow operations, too much transport and occupational hazards. Another problem seen by the team was that of poor scheduling which resulted to existence of idle machines and a not continuous workflow. Alternatives for solution to these problems were sought, examined and evaluated before the team finally specified the best solution. A new layout is proposed resulting to fewer transports and delays. A change in equipment was suggested to minimize manual handling of materials. The use of a schedule board was recommended to ensure adherence to the schedule. The objective of the second part of the study, Systems and Procedures, is to be able to apply the concepts learned in Methods Engineering in analyzing and existing system of the company. Data was gathered through interviews conducted with the people involved. Forms, their movement and the office layout were studied to facilitate the analysis of the existing system. The procedure from acceptance of order to shipment was studied and the different forms used were examined to give a better view of the existing system. The team sees the advantage of having the contractual workers learn all the machine operations. The advantage lies in the fact that there would be no scheduling problems especially lack of wonders available when a certain operation is needed to be done. Although the company has generally a good organizational set-up wherein the lines of responsibility and authority are clearly defined, the existing system shows an insufficient communication between departments especially between the Sales department, the one accepting orders from other companies and the Production department. The only link between the two is a note paper containing the order of the purchasing company. The team recommends the use of its proposed form for the acceptance of orders in the sales department. The form will contain the following information : the date the order was made, the name of the purchasing company, the sizes and types of cans ordered, the quantity for each type and size, the date of delivery and the name of the person who received the order. It is not enough that the sales department gives the order form and stops there. The sales department must have a schedule sheet and look at it or consult with a production supervisor before an order is accepted. This is to avoid having scheduling problems.